Future of the ChatGPT in Higher Education: New Insights From Young Researchers - Yilmaz, Ayse Merve Urfa; Yuceol, Nazli (TUBA-TURKISH ACAD SCIENCES, 2025)
This study investigates the perspectives of young researchers employed in higher educational institutions in & Idot;stanbul regarding the future use of ChatGPT. Qualitative research methodology was used in this study. To gather information, in-depth interviews were conducted with 20 young researchers from the fields of science and engineering, social sciences, and health sciences. The obtained data was analyzed using thematic analysis, which uncovered five main themes: future expectations, ethical practices, integration of ChatGPT into education and research, future concerns arising from ChatGPT, and benefits achieved from ChatGPT usage. The findings indicate that the employment of ChatGPT will be unavoidable in the future, and the discussion emphasizes the necessary steps for fostering its utilization. These steps are presented in a process framework. The process framework focuses on what actions to take and how to implement them. Accordingly, it has been identified that both students and academics need to be trained on the ethical and effective use of ChatGPT. After these trainings, ChatGPT should be integrated into education and teaching with various usage guides and application instructions. This research offers valuable insights into what can be done to promote the ethical, effective, and proper utilization of AI tools like ChatGPT in higher education.
Keywords: Artificial Intelligence (AI); ChatGPT; Future of ChatGPT; Higher Education; Young Researchers; Education & Educational Research